Pædagogiske ventepositioner – i socialpædagogisk praksis - Jørgensen, Sabine Ellung; Mauritzen, Britt Frik; Larsen, Lisbeth; Dam, Brian Cramon; Hegelund, Peter; Karlsmose, Jonas Elbæk (Tidsskrift for Professionsstudier, 2025)
This article explores the concept of ’pedagogical waiting positions’ as a central but often overlooked aspect of social pedagogical practice. The article challenges the perception of waiting time as a passive practice, demonstrating instead how pedagogical waiting - defined as shorter or longer periods during which the pedagogue remains in an anticipatory stance in their interaction with a citizen - contains significant pedagogical potential. The article distinguishes between activity-internal waiting positions, which support the continuation or resumption of an ongoing activity, and activity-external waiting positions, which arise in the transition between the end of one pedagogical activity and the beginning of another. We show how both types of waiting positions require an active and reflective interplay between observation, analysis, and readiness to act. Drawing on narratives, interviews, and video observations from a practice-based research project at a residential facility for individuals with significant physical and intellectual disabilities, we demonstrate how different orientations within waiting positions require mental, emotional, and physical awareness. The article concludes that recognizing waiting positions as a professional competence is crucial for enhancing the acknowledgment of social pedagogical work. Furthermore, the article highlights the need for managerial and collegial support that legitimizes waiting positions as an integral part of pedagogical professionalism and fosters critical reflections on practice.